Bridging Language Learning and Entrepreneurship: Examining Arabic Language Students’ Potential in Developing 'Arabic for Specific Purposes' Module Projects - Muslimah, Maziyyatul; Afyuddin, Moh Sholeh; Cahyono, Machrup Eko; Pradana, Satria Adi (Journal of Arabic Language Learning and Teaching (JALLT), 2025)
This research explores the potential of Arabic language students in Indonesia to develop "Arabic for Specific Purposes" (ASP) modules, focusing on integrating entrepreneurial concepts into language learning. The study aims to examine the factors influencing students' engagement in entrepreneurship and how a structured curriculum can enhance both their entrepreneurial skills and Arabic proficiency. Using a mixed-methods approach, the study surveyed 136 students from Arabic Language Education programs across various Indonesian universities, gathering both quantitative data on students' attitudes toward entrepreneurship and qualitative insights into their experiences in ASP module development. The findings revealed that most students show strong interest in creating practical Arabic modules, especially for real-world applications. However, they require further training in communication skills, curriculum design, and market awareness. The study suggests that incorporating entrepreneurial competencies into the curriculum—especially in market analysis and user-centered design—would benefit students. It recommends providing structured support and training to bridge knowledge gaps and enhance students' entrepreneurial potential. Future research could explore how gender dynamics and real-world entrepreneurial simulations influence ASP module development in language education.